FLUORESCENCE INVESTIGATION OF SOME POLYSTYRENE SAMPLES THERMALLY DEGRADED - NICULAESCU, Carmen; BREZESTEAN, Ioana; LUNG, Claudiu; TODICA, Mihai (Studia Universitatis Babeș-Bolyai Physica, 2018)
The behavior of some samples of commercial polystyrene, thermally degraded, was investigated by UV-VIS and fluorescence methods. Excited with different wavelengths in the domain 315-365 nm, the spectra show a peak located at 409 nm. The amplitude and the shape of this peak change after thermal degradation. Minor changes appear at 200ºC, indicating relatively stability of the samples, but the modifications are more important at 350ºC. At that temperature the samples are affected by oxidation.